الاختصاص التفسيري للمحكمة الدستورية في ظل التعديل الدستوري لسنة 2020 - هند، عماري (جامعة الوادي University of El Oued, 2024)
صياغة الدستور غالبا ما تكون بصورة مختصرة بعبارات عامة و مجردة، مما يعرضها للغموض و الإبهام و هذا ما يستدعي تفسيرها، ولضمان نزاهة و سلامة التفسير قام المؤسس الدستوري الجزائري باستحداث المحكمة الدستوري ضمن تعديل الدستور لسنة2020، والذي كرس بمقتضى المادة 192 منه التفسير الدستوري لأول مرة كاختصاص أصيل للمحكمة الدستورية باعتبارها أنسب هيئة لمباشرة الاختصاص التفسيري، بعد أن كان يمارس بطريقة غير مباشرة من قبل المجلس الدستوري إعمالا للرقابة الدستورية، متبعا تقنية التحفظات الدستورية كرقابة تصحيحية تحول دون إلغاء النص. حيث تتم عملية التفسير بناء على طلب من أحد الجهات المحددة في الدستور لإزالة أي لبس أو غموض قد يعتري حكم أو عدة أحكام دستورية، ورغم تأكيد المؤسس الدستوري في المادة 192 على إلزامية القرارات الصادرة بشأنها الرقابة على دستورية القوانين، إلا أنه لم يشر الى مدى إلزامية الآراء الصادرة عند ممارسة التفسير المباشر. The constitution is mostly drafted briefly,and in general, abstract terms, consequently, it is exposed to ambiguity and vagueness which poses the need for interpretation. In order to ensure the integrity and viability of the interpretation the Algerian constitution founder established the constitutional court within the constitutional amendment of 2020. Under the article 192, and for the first time, constitutional interpretation was appointed as an inherent jurisdiction of the constitutional court as the most appropriate entity to exercise the interpretive jurisdiction. This jurisdiction was previously practiced indirectly by the constitutional council to enforce constitutional monitoring, creating constitutional reservation technique as a corrective monitoring tool. In order to avoid the nullification of legal texts, the interpretation process is conducted based on the demand of one of the entities Specified by the constitution with the aim of clearing up any ambiguity that may affect one or several constitutional decisions. In spite of the emphasis of the constitutional founder on the compulsion of the resolutions issued concerning monitoring the constitutionality of laws, they did not point out the extent of compulsion when it comes to the opinions issued when practicing the interpretive jurisdiction of the constitutional.
ماستر قانون اداري